2014
DOI: 10.1007/s00467-014-2820-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of higher erythropoiesis stimulating agent dose and mortality in children on dialysis

Abstract: Background Higher doses of erythropoiesis-stimulating agents (ESA) have been associated with an increased risk of adverse outcomes in adults with chronic kidney disease (CKD) and end-stage kidney disease (ESRD), but to our knowledge no trials have been performed in children. We examined the association between ESA dose and all-cause mortality in a prevalent pediatric dialysis population. Methods Retrospective cohort study utilizing national data on all prevalent dialysis patients aged <18 years from the Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…In light of clinical trial data in adults regarding the adverse effects of using escalating ESA doses to treat resistant anemia [35,36], along with recent observational evidence in children on dialysis that higher ESA doses are associated with an increased risk for mortality [27,37], there is a need for adjunctive anemia therapies with the potential to delay the need for ESA initiation or allow effective use of lower doses to maintain adequate HGB levels and avoid the need for red blood cell transfusions. Elevated hepcidin levels may be useful to identify anemic patients who may respond to IV iron administration, a task for which traditional iron indices are of limited utility [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of clinical trial data in adults regarding the adverse effects of using escalating ESA doses to treat resistant anemia [35,36], along with recent observational evidence in children on dialysis that higher ESA doses are associated with an increased risk for mortality [27,37], there is a need for adjunctive anemia therapies with the potential to delay the need for ESA initiation or allow effective use of lower doses to maintain adequate HGB levels and avoid the need for red blood cell transfusions. Elevated hepcidin levels may be useful to identify anemic patients who may respond to IV iron administration, a task for which traditional iron indices are of limited utility [38].…”
Section: Discussionmentioning
confidence: 99%
“…RNA interference and gene silencing technologies to inhibit hepcidin gene transcription are under development in animal models, but are still quite remote from clinical application in humans [3941]. Anti-hepcidin monoclonal antibodies and L-RNA aptamers (Spiegelmers) which can inhibit hepcidin activity and overcome erythropoietin resistance in animal models have been developed, with some currently in Phase I human clinical trials [3537]. Interventions to prevent the endocytosis of ferroportin in response to binding by hepcidin are also in pre-clinical development [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, upregulation of HIF in the kidneys will drive secretion of erythropoietin (EPO), which dose dependently increases FGF23 mRNA and total protein (9). This might further explain the adverse effects of EPO or erythropoiesis stimulating agents during the course of CKD progression (47,82,84). This also suggests that multiorgan normoxic and hypoxic HIF-1␣ stabilization occurring in CKD might represent an alternative therapeutic target.…”
Section: Mechanisms For Fgf23 Regulation By Inflammationmentioning
confidence: 97%
“…Unlike the current study, they did not find an association between all-cause hospitalizations and hemoglobin, perhaps because of differences between the 2 studies including that the previous study was limited to children 12 years of age and older, producing a smaller overall cohort. Lestz et al 22 identified an association between higher ESA dosing and mortality in children on chronic dialysis that was independent of hemoglobin level. Our current study adjusted for EPO dosing and still found a lower risk for all-cause mortality in children with a hemoglobin level $12 g/dl.…”
Section: Discussionmentioning
confidence: 99%